Malaysia’s macro-financial strategy in reducing property wealth disparity and increasing property ownership affordability – who benefits more? - Abdul Hamid Mar Iman; Christopher Gan (2014)
The relationship of a country’s macro-financial strategy against property-based relative wealth (pbrW) disparity and property ownership affordability (poA) has not been analyzed before. These are perennial issues of any country since POA influences the level of pbrW disparity among the people. This paper addresses two issues. First, whether POA influences PBRW disparity or PBRW disparity influences POA or whether both have a bi-directional relationship. Second, whether the macro-financial strategy has any effect on PBRW disparity of the citizens. We used a sample of 36,349 individual market transactions of (mainly) residential and commercial properties over a 30-year period from 1982 to 2012. the study uses a vector autoregression to investigate the above issues. the result revealed that Malaysia’s macro-financial strategy has had different effects on PBRW disparity and property ownership affordability of the Malaysian main ethnics group (Malays). It benefited the non-Malays more than the Malays.